STUDI DESKRIPTIF PENGETAHUAN TENTANG PERAN KADER DALAM MENURUNKAN ANGKA KEMATIAN IBU MELALUI INOVASI ONE CLIENT ONE KADER SIASAT KEREN DI KABUPATEN BANJARNEGARA - Ratih Subekti; Dewie Sulistyorini (Siklus : Journal Research Midwifery Politeknik Tegal, 2022)
Maternal and child mortality is an indicator of a region's health. In 2018 there were 9 cases of maternal death in Banjarnegara district. The One Client One Cadre strategy method is a form of involving health cadres in monitoring the health of pregnant women in the local area which can help minimize the factors causing maternal and infant mortality. The purpose of this study was to determine the knowledge of cadres about the role of health cadres in reducing Maternal Mortality Rate (MMR) through the innovation of One Client One Kader strategy method at Banjarnegara District Health Center. The method used is descriptive analysis. Sampling based on non-probability sampling with accidental sampling technique as many as 67 people. The results showed that the respondents were dominated by the age of 30-39 years as many as 31 people (46.3%), high school education / equivalent as many as 30 people (44.8%) and the status of not working as many as 49 people (73.1%). The most knowledge about reminding pregnant women to check pregnancy with "good" knowledge 28 people (41.8%), about how to detect risk factors in pregnant women the most with "good" knowledge 34 people (50.8%), about fetal monitoring the most with "good" knowledge 42 people (62.7%) and about P4K commitment the most with "good" knowledge is 32 people (47.8%).Keywords: cadres, knowledge, One Client One Kader (Oce Oke)